Robotic-arm assisted partial knee arthroplasty: a single centre experience - Marcovigi, Andrea; Zambianchi, Francesco; Sandoni, Dario; Rivi, Elisa; Catani, Fabio (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: UKA has proven to be an effective surgical procedure, but its survivorship is still negatively affected by inaccuracy in component component positioning, implant and limb alignment. Robotic surgery has been introduced in order to minimize such technical errors. The aim of the present paper was to evaluate clinical and surgical outcomes after a 3 years’ experience of robotic assisted UKA with the Mako Robotic Arm. Methods: Seventy-three patients undergoing  UKA with robotic instrumentation (65 medial UKAs, 8 lateral UKAs) and with a clinical follow-up of 3 -37 months were included in the present study. A complete clinical evaluation with KOOS, FJS-12 and SF-12 was administered to all patients pre and post operatively. Post-operative HKA angle and surgical time were also recorded. Results: Mean post-operative KOOS score was 81.32 (SD 17.19), while the mean FJS-12 score was 75.51 (SD 30.12) and the mean SF-12 Physical Score 42.25 (SD 9.97). 91% to 88% of post-operative results were considered satisfactory. Only 1 UKA failure was reported (1.3%) caused by peri-prosthetic infection. In medial UKAs mean postoperative HKA angle in extension was 3.9° varus (SD 2.5°), with no case of overcorrection; in lateral UKAs mean postoperative HKA angle in extension was 1.9° valgus (SD 1.9°) with 1 case (13%) of overcorrection. Mean skin to skin surgical time decreased from 83.2 minutes (SD 13.0) to 70.0 minutes (SD 10.9) along the learning curve. Conclusions: Robotic UKA has provided an improvement both in clinical and technical results, determining satisfactory clinical outcomes and a low risk of post-operative complications.